Design of Phinisi Tourism for IKN-Balikpapan Bay Route - Alamsyah, Alamsyah; Abdillah, Riza; Suardi; Sitorus, Chris Jeremy Verian; Kustiwansa, Harlian; Hariyono (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Balikpapan Bay connects Balikpapan City with the new capital city of the Republic of Indonesia (IKN). Currently, many community activities in Balikpapan Bay include functioning as a crossing, loading and unloading, and fishing. Balikpapan Bay also offers an unforgettable water tourism experience with many intriguing attractions for all ages, such as water slides and diving. IKN is utilized by the development of marine transportation to create marine tourism potential in Balikpapan Bay. The purpose of the research project is to build a tourist phinisi ship that allows tourists from within and outside the country to spend their free time on board and enjoy the splendor of Balikpapan City and IKN with a cultural concept. Phinisi will be equipped with lodging, museums, cafes, and restaurants, all depending on the design of the boat. The research stages include designing a general arragement that produces data in the form of main dimensions, hull form coefficients, lines plans, general arrangements, 3D designs, and interior rooms. The research method used is the parentship approach. The main dimensions obtained in my final assignment include; loa = 55 m, B = 9 m, H = 5 m, T = 3.5 m, Vs = 9 Knots, Crew 11 people, passengers = 15 people